Polyolefin microporous membrane, separator for secondary battery, and secondary battery
By coexisting highly oriented and low melting temperature polyolefin molecular chain structures in the polyolefin microporous membrane, the problem of insufficient mechanical strength at high temperatures is solved, and the safety of the battery separator is significantly improved.
Patent Information
- Application Number
- CN202380047713.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-27
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-14
AI Technical Summary
The existing polyolefin microporous membranes are insufficient in mechanical strength at high temperatures, resulting in reduced battery safety, especially when the battery is abnormally heated, it is more prone to short circuits and fires.
By coexisting highly oriented polyolefin molecular chain structures and structures at low melting temperatures in polyolefin microporous membranes, high mechanical strength is ensured to remain at high temperatures. The specific implementation method includes determining a specific temperature difference in the crystalline melting heat through differential scanning calorimetry analysis, and controlling the molecular chain orientation and melting characteristics of the polyolefin during the film making process.
The high mechanical strength of the polyolefin microporous membrane under high temperature conditions is achieved, the safety of the battery separator is enhanced, and short circuits and fires are prevented.
Smart Images

Figure BDA0005192332350000141 
Figure BDA0005192332350000151
Abstract
Description
Technical Field
[0001] The present invention relates to a polyolefin microporous film, a separator for a secondary battery, and a secondary battery. Background Art
[0002] Microporous membranes are used in a variety of fields, such as filters such as filtration membranes and dialysis membranes, battery separators, and electrolytic capacitor separators. Among them, polyolefin microporous membranes made of polyolefin resin materials are widely used as separators for secondary batteries because of their excellent chemical resistance, insulation, and mechanical strength, as well as their shutdown properties.
[0003] When using a polyolefin microporous membrane as a separator for a secondary battery, its performance is closely related to battery characteristics, battery productivity and battery safety. Therefore, the polyolefin microporous membrane requires excellent ion permeability, mechanical properties, heat shrinkage resistance, shutdown characteristics, fuse characteristics, etc. Among them, mechanical properties and fuse characteristics have a great influence on the safety of the battery, so they are particularly valued items. In order to suppress the thermal runaway of the battery, the pore occlusion of the diaphragm at high temperature and the current flowing between the electrodes is cut off, which is called shutdown. The lower the temperature of the shutdown, the more the thermal runaway risk of the battery is suppressed. In addition, in order to prevent the rupture of the polyolefin microporous membrane generated when foreign matter is mixed into the winding body or the battery or mechanical deformation is applied to the battery as a whole, and the battery short circuit generated therewith, high mechanical strength is required. The shutdown characteristics and mechanical strength are basically a trade-off relationship, so that the two characteristics coexist at a high level and become one of the topics of polyolefin microporous membranes.
[0004] Here, since secondary batteries such as lithium-ion secondary batteries have high energy density, they are widely used as batteries for motor drive power supplies, stationary storage batteries, etc. for personal computers, portable phones, and then electric vehicles or hybrid vehicles. In recent years, with the goal of further high performance, the high density of energy density of secondary batteries is required. In order to increase the volume of electrodes, it is hoped that the membrane will be thin and high-capacity electrodes will be applied. However, in general, when the diaphragm becomes a thin film, it will lose mechanical strength, so it is easy to cause the diaphragm to rupture due to foreign matter mixed in the winding body or the battery or mechanical deformation applied to the battery as a whole, and cause short circuit, which has a tendency to reduce safety. In particular, when the battery is abnormally heated and high-temperature, the strength of the polyolefin microporous membrane is further reduced, so it is more likely to short-circuit, resulting in an increased risk of battery fire or explosion. Based on the above background, it is strongly required that the mechanical strength of the polyolefin microporous membrane used in the battery diaphragm is further improved, especially when the battery is high-temperature, it also has high mechanical strength.
[0005] For example, Patent Document 1 discloses a polyolefin microporous membrane having a shutdown temperature of 135°C or less and a crystal melting rate of 50% or less at the shutdown temperature, and describes a battery separator having excellent shutdown characteristics and high safety. In addition, Patent Document 2 discloses a polyolefin microporous membrane, which is a single-layer polyolefin microporous membrane containing polyethylene and polyolefins other than polyethylene, has a membrane thickness of 8 μm or less, a shutdown temperature of 135°C or less, and a melting temperature of 160°C or more, and describes a battery separator having excellent safety and output characteristics. In addition, Patent Document 3 discloses a polyolefin microporous membrane, characterized in that it contains polyethylene with a molecular weight of less than 10,000 in a molar ratio of 8 to 60 wt%, a ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) Mw / Mn of greater than 11 and less than 100, and a viscosity average molecular weight (Mv) of greater than 100,000 and less than 1,000,000, and polyethylene with Mw / Mn of greater than 1 and less than 10 and Mv of greater than 10,000 and less than 500,000. The polyolefin microporous membrane has a molecular weight of less than 10,000 in a molar ratio of 8 to 60 wt%, a porosity of 20 to 95%, and a heat shrinkage at 100°C of less than 10%, and records a battery separator that can provide excellent pore occlusion, heat shrinkage and high temperature strength.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2020 / 195380
[0009] Patent Document 2: International Publication No. 2021 / 033733
[0010] Patent Document 3: Japanese Patent Application Publication No. 2006-321841 Summary of the invention
[0011] Problems to be solved by the invention
[0012] However, although the polyolefin microporous membranes described in Patent Documents 1 or 2 have high mechanical strength and shutdown characteristics at room temperature, it is desirable to further improve the mechanical strength at high temperature from the perspective of safety when the battery is heated to high temperature. In addition, the polyolefin microporous membrane of Patent Document 3 has excellent shutdown characteristics, but the mechanical strength at room temperature tends to decrease accordingly. In addition, the mechanical strength at higher temperatures is insufficient for the current batteries with high energy density.
[0013] As mentioned above, various studies have been conducted on polyolefin microporous membranes with the purpose of having both mechanical strength and shutdown characteristics at room temperature at a high level. However, it is still difficult to achieve high mechanical strength at high temperatures on this basis. Even at high temperatures, polyolefin microporous membranes have excellent shape retention characteristics, even in the case of abnormal heating of the battery, and are difficult to break and have high durability even if foreign matter is mixed into the winding body or the battery or mechanical deformation is applied to the battery as a whole, so short circuits can be suppressed and battery safety can be improved, so they are highly anticipated.
[0014] Therefore, the present invention focuses on the increasing safety requirements for separators as the energy density of secondary batteries increases, and aims to provide a polyolefin microporous membrane that has high mechanical strength even at high temperatures and is highly safe even when the battery temperature increases when used as a battery separator.
[0015] Solution
[0016] The present inventors have conducted repeated and intensive studies to solve the above-mentioned problems, and as a result, have found that by allowing a highly oriented structure of polyolefin molecular chains constituting the polyolefin microporous membrane, which contributes to the mechanical strength of the polyolefin microporous membrane, and a polyolefin having a structure that melts at a temperature lower than the melting temperature of the polyolefin having the highly oriented structure to coexist in the polyolefin microporous membrane, the membrane can have high mechanical strength even when closed at high temperatures, thereby completing the present invention.
[0017] That is, the present invention solves the problem by the following means.
[0018] [I] A polyolefin microporous membrane, wherein the temperature at which the crystal melting endotherm measured in the first heating process by differential scanning calorimetry becomes 50% of the total melting endotherm is denoted as T 50 The temperature at which 10% of the total melting heat is absorbed is recorded as T 10 When the polyolefin microporous membrane satisfies T 50 -T 10 ≥15℃, when the strength at the time of displacement of 5mm in the puncture strength measurement conducted at the closed temperature is recorded as PS5, PS5 is 7.0gf / g / m 2 above.
[0019] [II] The polyolefin microporous membrane according to [I], having a puncture strength of 55 gf / g / m2 measured at 25°C in terms of mass per unit area. 2 above.
[0020] [III] The polyolefin microporous membrane according to [I] or [II], wherein the melting point measured in the first heating process by differential scanning calorimetry is 130° C. or higher and 140° C. or lower.
[0021] [IV] The polyolefin microporous membrane according to any one of claims [I] to [III], wherein the tensile strength in the width direction TD measured at 25°C is 2100 kgf / cm 2 above.
[0022] [V] The polyolefin microporous membrane according to any one of claims [I] to [IV], which has a shutdown temperature of less than 133°C.
[0023] [VI] The polyolefin microporous membrane according to any one of claims [I] to [V], wherein the membrane thickness is 10 μm or less.
[0024] [VII] The polyolefin microporous membrane according to any one of claims [I] to [VI], wherein the polyolefin constituting the polyolefin microporous membrane contains polyethylene as a main component.
[0025] [VIII] A secondary battery separator comprising the polyolefin microporous membrane according to any one of [I] to [VII].
[0026] [IX] A secondary battery comprising the secondary battery separator described in [VIII].
[0027] Effects of the Invention
[0028] The polyolefin microporous membrane of the present invention is excellent in mechanical strength at high temperatures, and therefore, when used as a battery separator, it is possible to maintain high safety even when the battery temperature is increased. DETAILED DESCRIPTION
[0029] The present embodiment of the present invention will be described below. Note that the present invention is not limited to the embodiment described below.
[0030] 1. Polyolefin microporous membrane
[0031] Next, the polyolefin microporous membrane of this embodiment will be described.
[0032] (Heat absorption of melting of polyolefin microporous membrane)
[0033] In the polyolefin microporous membrane of the present invention, in the curve of the crystal melting endotherm measured in the first temperature rise process (first heating process) by a differential scanning calorimeter (DSC) according to the measurement method described below (the vertical axis is the crystal melting endotherm and the horizontal axis is the temperature), the temperature at which the crystal melting endotherm becomes 10% of the total melting endotherm is recorded as T. 10 , and the temperature at which it will become 50% is recorded as T 50 When T 50 -T 10 Above 15℃.
[0034] T 50 -T 10 The value of is more preferably 17°C or higher, and further preferably 19°C or higher. The upper limit is preferably 30°C or lower, and more preferably 25°C or lower. 10 It indicates the temperature at which the crystal melting of the polyolefin microporous membrane progresses to a certain extent when the polyolefin microporous membrane is heated. 50 It indicates the temperature at which the crystal melting of the polyolefin microporous membrane is more than halfway completed when the polyolefin microporous membrane is heated. 50 -T 10 If the value of T is within the above range, even if the polyolefin microporous membrane is closed and part of the resin is melted, a highly oriented structure remains and high mechanical strength can be maintained. 50 -T 10 The value of is less than 15°C, since most of the oriented structure melts during shutdown, the mechanical strength cannot be maintained at a high level. 50 -T 10 If the value of T exceeds 30°C, the melting temperature of the film may be different, resulting in poor film forming properties. 50 -T 10 The method for setting the value of to the above range is not particularly limited, and examples thereof include applying a polyolefin having a specific melting point (having two or more melting points in the range of 105 to 125° C. and in the range of 130 to 140° C.) to the polyolefin used as the raw material.
[0035] (Strength at 5 mm displacement in puncture strength measurement at closing temperature)
[0036] When the strength at a displacement of 5 mm in the puncture strength measurement at the shutdown temperature of the polyolefin microporous membrane is referred to as PS5, the lower limit of PS5 is 7.0 gf / g / m 2 More than 8.0 gf / g / m 2 More preferably 9.0 gf / g / m 2 There is no specific upper limit for PS5, for example, 15.0 gf / g / m2 PS5 is a polyolefin microporous membrane in the above range, which has excellent membrane strength and shape retention characteristics even at high temperatures and has high durability that is difficult to break. For example, a secondary battery using the polyolefin microporous membrane as a separator can suppress the occurrence of battery short circuits. If PS5 is less than 7.0 gf / g / m 2 , then the membrane strength is insufficient at high temperature, and the risk of battery short circuit increases. There is no particular limitation on the method for setting the value of PS5 to the above range, and methods such as controlling the orientation of the molecular chains of the polyolefin constituting the polyolefin microporous membrane can be cited. In addition, if the orientation of the molecular chains of the polyolefin constituting the polyolefin microporous membrane is improved, the value of PS5 tends to increase.
[0037] (Puncture strength calculated by mass per unit area)
[0038] The lower limit of the puncture strength of the polyolefin microporous membrane in an atmosphere at 25° C., calculated as the mass per unit area, is preferably 55 gf / g / m 2 More preferably 57gf / g / m 2 More preferably, 59 gf / g / m 2 There is no particular upper limit on the puncture strength converted to unit area mass, but it is, for example, 90 gf / g / m 2 . When the puncture strength converted to the mass per unit area is within the above range, the polyolefin microporous membrane has excellent membrane strength. For example, in a secondary battery using the polyolefin microporous membrane as a separator, even if foreign matter is mixed into the winding body or the battery, the separator will not break, and the occurrence of electrode short circuit can be suppressed. In addition, when manufacturing a secondary battery, the separator can be wound while applying high tension, so the winding density of the three-layer film consisting of the negative electrode, the separator and the anode can be increased, and the high capacity of the secondary battery can be achieved. In order to set the value of the puncture strength converted to the mass per unit area to the above range, it is preferred to set the composition of the polyolefin microporous membrane and the stretching conditions during film preparation to the range described later.
[0039] (Melting Point of Polyolefin Microporous Membrane)
[0040] The melting point of the polyolefin microporous membrane is defined as the temperature of the peak confirmed in the curve of the melting endotherm determined by the first heating process (first heating process) of DSC according to the measurement method described later. The lower limit of the melting point of the polyolefin microporous membrane is preferably above 130°C, more preferably above 132°C, and further preferably above 134°C. The upper limit of the melting point is preferably below 140°C, more preferably below 138°C. If the melting point temperature is low, the low melting point of the polyolefin microporous membrane can be achieved, but there is a risk of becoming a low-oriented structure and reduced strength. In addition, if the melting point temperature is high, it becomes a more highly oriented structure, which can improve the strength, but there is also a risk of rising shutdown temperature. In order to make the melting point temperature within the above range, it is preferred to set the composition of the polyolefin microporous membrane and the stretching conditions during film formation to the range described later.
[0041] (Tensile strength in width direction (TD))
[0042] The lower limit of the tensile strength of the polyolefin microporous film in the width direction (TD) at 25° C. is preferably 2100 kgf / cm 2 More preferably 2300kgf / cm 2 More preferably, 2500 kgf / cm 2 The upper limit of the tensile strength in the width direction (TD) is not particularly limited, but is, for example, 3000 kgf / cm 2 . When the tensile strength in the width direction (TD) of the polyolefin microporous membrane is within the above range, it is difficult to break even when high tension is applied to the polyolefin microporous membrane, and it has high durability. For example, a secondary battery using the polyolefin microporous membrane as a separator can suppress the occurrence of battery short circuits even when subjected to external impacts. In addition, when a coating is formed on at least one surface of the polyolefin microporous membrane, a higher tensile strength is required for the polyolefin microporous membrane. Therefore, from the viewpoint of improving the coating property, when the tensile strength is within the above range, the polyolefin microporous membrane can be well used as a substrate for coating. In order to set the value of the tensile strength in the width direction (TD) to the above range, it is preferred to set the composition of the polyolefin microporous membrane and the stretching conditions during film formation to the range described later.
[0043] (Shut-off temperature)
[0044] The shutdown property of the polyolefin microporous membrane is to measure the air permeability resistance obtained by heating to a detection limit of 1×10 5 sec / 100cm 3The temperature at Air is evaluated as the shutdown temperature. The shutdown temperature of the polyolefin microporous membrane is preferably above 110°C and less than 133°C, more preferably above 110°C and below 132.5°C, and further preferably above 110°C and below 132°C. When the shutdown temperature is less than 133°C, compared with the previous polyolefin microporous membrane, it is possible to suppress thermal runaway of the battery at high temperatures and improve safety. In addition, when the shutdown temperature is less than 110°C, for example, there is a risk of thermal stability when it is configured near the high-temperature part of the vehicle, and there is a risk of a sharp deterioration in air permeability during heat setting. In order to set the shutdown temperature to the above range, it is preferred to set the composition of the polyolefin microporous membrane and the stretching conditions during film formation to the range described below.
[0045] (film thickness)
[0046] The upper limit of the film thickness of the polyolefin microporous membrane is preferably 10 μm or less, more preferably 9 μm or less, and further preferably 8 μm or less. There is no particular limitation on the lower limit of the film thickness, for example, it is preferably 1 μm or more, and more preferably 3 μm or more. If the film thickness is within the above range, when the polyolefin microporous membrane is used as a battery separator, the electrode size can be increased and the battery capacity can be improved.
[0047] (Mass per unit area)
[0048] The upper limit of the mass per unit area of the polyolefin microporous membrane is not particularly limited, but is preferably 6.5 g / m 2 Below, preferably 6.0 g / m 2 There is no particular lower limit on the mass per unit area, but it is, for example, 1.0 g / m 2 More preferably 1.5 g / m 2 When the mass per unit area of the polyolefin microporous membrane is within the above range, when the polyolefin microporous membrane is used as a separator, the amount of electrolyte retained per unit volume can be increased, thereby ensuring high ion permeability. 2 The quality of the polyolefin microporous membrane.
[0049] (Enthalpy of the second heating process of DSC)
[0050] The polyolefin microporous membrane preferably has a peak temperature (peak top temperature) with the largest melting endotherm among the peaks confirmed in the curve of melting endotherm measured by the second temperature increase process (second heating process) of DSC in the range of 130 to 140°C, and a crystalline melting endotherm of 120°C or less is 17.5% or more of the total crystalline melting endotherm. In the curve of melting endotherm measured by the second temperature increase process (second heating process) of DSC, when the temperature of the peak with the largest melting endotherm becomes higher, it means that the structure that becomes the basic skeleton in the polyolefin microporous membrane is stable at high temperature, so T50 tends to be high temperature. In addition, in the curve of melting endotherm measured by the second temperature increase process (second heating process) of DSC, the crystal melting endotherm of 120°C or less accounts for a certain ratio relative to the total crystal melting endotherm, which means that the polyolefin microporous membrane contains a certain amount of a structure (low melting point component) that melts at low temperature. In the curve of the melting endotherm measured by the second temperature rise process (second heating process) of DSC, if the ratio of the crystal melting endotherm below 120°C to the total crystal melting endotherm is increased, T10 tends to be lowered. The method of making the temperature of the peak with the largest melting endotherm in the range of 130 to 140°C and the crystal melting endotherm below 120°C 17.5% or more of the total crystal melting endotherm is not particularly limited, and examples thereof include a method of using one raw material with a controlled molecular weight distribution, a method of using two raw materials of a low molecular weight component and a high molecular weight component, etc. It is more preferred that the peak top temperature is in the range of 132 to 139°C and the crystal melting endotherm below 120°C is 18% or more and 30% or less of the total crystal melting endotherm, and it is further preferred that the peak top temperature is in the range of 134 to 138°C and the crystal melting endotherm below 120°C is 18.5% or more and 25% or less of the total crystal melting endotherm. The curve of the crystal melting endotherm measured by the first temperature rise process (first heating process) of DSC is greatly affected by the degree of orientation of the resin constituting the polyolefin microporous membrane, whereas the curve of the crystal melting endotherm measured by the second temperature rise process (second heating process) of DSC mainly represents the characteristics of the raw material constituting the polyolefin microporous membrane. By setting the ratio of the peak top temperature and the crystal melting endotherm below 120°C to the above range, in addition to having a highly oriented structure, there is also a structure that melts at a temperature lower than the temperature at which the highly oriented structure melts, so it is easy to set the value of T50-T10 to 15% or more.
[0051] (composition)
[0052] The polyolefin microporous membrane contains polyolefin as the main component. Containing as the main component means that it is contained as the largest component. Relative to 100% by weight of the polyolefin microporous membrane, it is preferably contained more than 90% by weight of polyolefin. Polyolefins can include, for example, polyethylene, polypropylene, etc. Among them, the polyolefin constituting the polyolefin microporous membrane preferably uses polyethylene as the main component. As polyethylene in this case, various polyethylenes can be used, and ultra-high molecular weight polyethylene, high-density polyethylene, branched high-density polyethylene, medium-density polyethylene, branched low-density polyethylene, linear low-density polyethylene, etc. can be listed. From the viewpoint of simultaneously improving the mechanical strength of the polyolefin microporous membrane and improving the shutdown characteristics, ultra-high molecular weight polyethylene is more preferably used. Polyethylene can be an ethylene homopolymer or a copolymer of ethylene and other α-olefins. As α-olefins, propylene, 1-butene, 1-hexene, 1-pentene, 4-methyl-1-pentene, octene, etc. can be listed. Relative to 100% by weight of the polyolefin microporous membrane, polyethylene can contain more than 50% by weight.
[0053] (Melting Point of Polyolefin Used for Polyolefin Microporous Membrane)
[0054] The polyolefin used in the polyolefin microporous membrane of the present invention preferably has a specific melting point (two or more melting points in the range of 105 to 125°C and in the range of 130 to 140°C). The melting point of the polyolefin used in the polyolefin microporous membrane is defined as the temperature of the peak confirmed in the curve of the melting endotherm measured by the second temperature rise process (second heating process) of DSC measured by the measurement method described below. By having a melting point in the above range, it is easy to 50 -T 10 The value of is set to the above range. There is no particular limitation on the method for controlling the melting point of the polyolefin used for the polyolefin microporous membrane of the present invention, and methods for controlling the weight average molecular weight, molecular chain skeleton, etc. of the polyolefin can be cited. For example, if the weight average molecular weight of the polyolefin increases, the melting point tends to increase, and if the weight average molecular weight decreases, the melting point tends to decrease. In addition, when there are more straight chain components in the molecular chain of the polyolefin, the melting point tends to increase, and the more branches in the molecular chain, the lower the melting point tends to become. As the polyolefin, a single component can be used, or a plurality of components can be mixed and used.
[0055] As required, polyolefin may contain other resin components except polyethylene and polypropylene. As other resin components, for example, resins imparting heat resistance may be used. In addition, various additives such as antioxidants, heat stabilizers, antistatic agents, ultraviolet light absorbers, antiblocking agents, fillers, crystal nucleating agents, and crystallization delay agents may also be contained within the scope of not damaging the effects of the present invention.
[0056] 2. Method for producing polyolefin microporous membrane
[0057] The manufacturing method suitable for use when manufacturing the polyolefin microporous membrane of the present invention can use a known method for manufacturing a polyolefin microporous membrane. As the method for manufacturing a polyolefin microporous membrane, for example, a dry film-making method and a wet film-making method can be cited. As the method for manufacturing the polyolefin microporous membrane of the present embodiment, from the viewpoint of controlling the structure and physical properties of the membrane, a film-making method combining a wet method and a dry method is preferred.
[0058] Hereinafter, a method for producing a polyolefin microporous membrane will be described. In addition, the following description is an example of the production method and is not limited to this method.
[0059] The method for producing a polyolefin microporous membrane in an embodiment of the present invention preferably includes the following steps (1) to (5), may further include the following step (6), and may further include the following step (7).
[0060] (1) A step of preparing a polyolefin resin composition by melt-kneading the above-mentioned polyolefin resin and a film-forming solvent.
[0061] (2) A step of extruding the polyolefin resin composition and cooling it to form a gel-like sheet.
[0062] (3) A first stretching step of stretching the gel-like sheet.
[0063] (4) A step of removing the film-forming solvent from the stretched gel-like sheet.
[0064] (5) A step of drying the sheet after the film-forming solvent has been removed.
[0065] (6) A second stretching step of stretching the dried sheet.
[0066] (7) A step of heat-treating the dried sheet.
[0067] Below, each process is described separately.
[0068] (1) Preparation step of polyolefin resin composition
[0069] First, a polyolefin and a film-forming solvent are melt-kneaded to prepare a polyolefin resin composition. As a melt-kneading method, for example, a method using a twin-screw extruder described in the specifications of Japanese Patent Nos. 2132327 and 3347835 can be used. The melt-kneading method is well known, so its description is omitted.
[0070] In addition, the polyolefin resin composition may contain ingredients other than the above-mentioned polyolefin and film-forming solvent, for example, a crystal nucleating agent (nucleating agent), an antioxidant, etc. As the nucleating agent, there is no particular limitation, and known compound-based crystal nucleating agents, microparticle-based crystal nucleating agents, etc. can be used. As an addition method, a masterbatch prepared by mixing the nucleating agent in advance into the polyolefin and dispersing it can be used.
[0071] (2) Gel Sheet Formation Step
[0072] Next, the molten resin is extruded and cooled to form a gel-like sheet. For example, the polyolefin resin composition prepared above is fed from an extruder to a die head and extruded into a sheet to obtain a molded body. The obtained molded body is cooled to form a gel-like sheet.
[0073] As a method for forming a gel-like sheet, for example, the method disclosed in Japanese Patent Gazette No. 2132327 and Japanese Patent Gazette No. 3347835 can be used. Cooling is preferably carried out at a rate of 50°C / min or more at least before the gelation temperature. Cooling is preferably carried out to below 25°C. By cooling, the microphase of the polyolefin separated by the film-making solvent can be fixed. When the cooling rate is within the above range, the crystallinity is maintained within an appropriate range, and a gel-like sheet suitable for stretching is obtained. As a cooling method, a method of contacting with a cooling medium such as cold air, cooling water, a method of contacting with a cooling roller, etc. can be used, but it is preferably cooled by contacting with a roller cooled by a cooling medium.
[0074] (3) First stretching step
[0075] Next, the gel-like sheet is stretched. The stretching of the gel-like sheet (first stretching) is also called wet stretching. The wet stretching is performed at least along one axial direction. Since the gel-like sheet contains a solvent, it can be stretched uniformly. The gel-like sheet is preferably stretched at a specified ratio by a tentering method, a roller method, a blow molding method or a combination thereof after heating. The stretching can be either uniaxial stretching or biaxial stretching, but biaxial stretching is preferred. In the case of biaxial stretching, it can be any of simultaneous biaxial stretching, successive stretching and multi-stage stretching (for example, a combination of simultaneous biaxial stretching and successive stretching).
[0076] The final area stretching ratio (surface ratio) in wet stretching is preferably more than 36 times, more preferably more than 42 times, and further preferably more than 49 times. The upper limit of the final area stretching ratio is preferably less than 100 times, more preferably less than 90 times. In addition, the final area stretching ratio in any direction of the length direction (machine direction: MD direction) and the transverse direction (width direction: TD direction) is preferably more than 5 times, and the stretching ratios in the MD direction and the TD direction can be the same or different from each other. If the final area stretching ratio is more than 36 times, a structure with a high degree of orientation of the molecular chain is formed, and it is possible to expect the improvement of mechanical strength such as puncture strength and tensile strength. If the final area stretching ratio is less than 36 times, the molecular chain cannot be fully oriented, and the structure is not developed, so the mechanical strength cannot be improved. In addition, the wet stretching ratio refers to the stretching ratio of the gel-like sheet after wet stretching when the gel-like sheet before wet stretching is used as the benchmark.
[0077] The lower limit of the stretching temperature is preferably in the range of +5°C or more, preferably +7°C or more, and more preferably +9°C or more, from the temperature at which the crystal melting endotherm becomes 10% of the total crystal melting endotherm in the curve of the crystal melting endotherm measured by the second temperature rise process of DSC of the gel-like sheet. The upper limit of the stretching temperature is +20°C or less, more preferably 17°C or less, from the temperature at which the crystal melting endotherm becomes 10% of the total crystal melting endotherm in the curve of the crystal melting endotherm measured by the second temperature rise process of DSC of the gel-like sheet. When the stretching temperature is within the above range, a structure melted at a relatively low temperature can be stretched in a melted state, and a structure melted at a higher temperature can be stretched in a state where the molecules are relaxed. As a result, a stretched sheet in which a structure with highly oriented molecular chains and a structure melted at a relatively low temperature exist independently can be easily obtained.
[0078] By stretching as described above, cracks are generated between the polyolefin layers, the polyolefin phase is fined, and a large number of fibrils are formed. The fibrils form a three-dimensional irregularly connected mesh structure.
[0079] (4) Removal of film-forming solvent
[0080] Next, the film-forming solvent is removed from the stretched gel-like sheet to form a polyolefin microporous membrane (membrane). The removal of the film-forming solvent is carried out by washing with a cleaning solvent. Since the polyolefin phase and the film-forming solvent phase are phase-separated, the film-forming solvent is removed to obtain a porous film having three-dimensional irregularly connected pores (voids) composed of fibrils forming a fine three-dimensional mesh structure. The cleaning solvent and the removal method of the film-forming solvent using the cleaning solvent are well known, so the description thereof is omitted. For example, the method disclosed in Japanese Patent No. 2132327 Specification or Japanese Patent Publication No. 2002-256099 can be used.
[0081] (5) Drying
[0082] Next, the polyolefin microporous membrane from which the membrane-forming solvent has been removed is dried by a heat drying method or an air drying method. The drying temperature is preferably below the crystal dispersion temperature (Tcd) of the polyolefin, and is particularly preferably 5°C or more lower than Tcd. Here, the crystal dispersion temperature (Tcd) refers to a value obtained by measuring the temperature characteristics of dynamic viscoelasticity based on ASTM D4065. For example, the above-mentioned ultra-high molecular weight polyethylene, and polyethylene and polyethylene compositions other than ultra-high molecular weight polyethylene have a crystal dispersion temperature of about 90 to 100°C. Taking the polyolefin microporous membrane as 100% by weight (dry mass), the drying is preferably carried out until the residual washing solvent becomes less than 5% by weight, and more preferably to less than 3% by weight. If the residual washing solvent is within the above range, the porosity of the polyolefin microporous membrane is maintained and the reduction of ion permeability is suppressed during the second stretching step and heat treatment step of the polyolefin microporous membrane in the next step.
[0083] (6) Second stretching step
[0084] The dried polyolefin microporous membrane can be stretched in at least one axial direction as needed. The stretching of the polyolefin microporous membrane can be carried out by a tentering method, a roller method, a blow molding method, etc. while heating as in the first stretching step. The stretching can be uniaxial stretching or biaxial stretching. In the case of biaxial stretching, it can be any of simultaneous biaxial stretching and sequential stretching.
[0085] There is no particular limitation on the stretching temperature in this process, which is usually 90 to 135°C, more preferably 95 to 130°C. The upper limit of the area stretching ratio in this process is preferably 16.0 times or less, more preferably 4.0 times or less, and further preferably 2.0 times or less. In the case of biaxial stretching, the stretching ratios in the MD direction and the TD direction may be the same or different from each other. In addition, the stretching ratio in this process refers to the stretching ratio of the polyolefin microporous membrane to be supplied to the next process, based on the polyolefin microporous membrane to be subjected to this process.
[0086] (7) Heat treatment
[0087] In addition, the dried polyolefin microporous membrane can also be heat treated. The crystallization is stabilized and the layered structure is uniformed by heat treatment. As a heat treatment method, at least one of heat setting treatment and heat relaxation treatment can be used. The so-called heat setting treatment is a heat treatment in which the two ends in the TD direction are kept constant so that the size of the membrane in the TD direction is unchanged while heating. The heat setting treatment is preferably carried out by a tenter method or a roller method. The so-called heat relaxation treatment is a heat treatment in which the membrane is thermally shrunk in the MD direction or the TD direction during heating. For example, as a heat relaxation treatment method, the method disclosed in Japanese Patent Gazette No. 2002-256099 can be cited. The heat treatment temperature is preferably in the range of (Tcd) to (melting point) of the polyolefin resin, more preferably in the range of ±5°C of the stretching temperature of the polyolefin microporous membrane, and particularly preferably in the range of ±3°C of the second stretching temperature of the polyolefin microporous membrane.
[0088] The polyolefin microporous membrane may be a single layer, or may be a layer composed of one or more polyolefin microporous membranes. A multilayer polyolefin microporous membrane may have two or more layers composed of polyolefin microporous membranes. In the case of a multilayer polyolefin microporous membrane, the composition of the polyolefin resin constituting each layer may be the same composition or different compositions.
[0089] In addition, other porous layers can also be stacked on the polyolefin microporous membrane of the present invention to form a multilayer porous membrane. As other porous layers, there is no particular limitation, for example, porous layers such as inorganic particle layers containing adhesives and inorganic particles can also be stacked. As the adhesive component constituting the inorganic particle layer, there is no particular limitation, and known components can be used, for example, acrylic resins, polyvinylidene fluoride resins, polyamide-imide resins, polyamide resins, aromatic polyamide resins, polyimide resins, etc. can be used. As the inorganic particles constituting the inorganic particle layer, there is no particular limitation, and known materials can be used, such as aluminum oxide, boehmite, barium sulfate, magnesium oxide, magnesium hydroxide, magnesium carbonate, silicon, etc. can be used. In addition, as a multilayer polyolefin porous membrane, it can also be a film formed by laminating the above-mentioned porous adhesive resin on at least one surface of the polyolefin microporous membrane.
[0090] 3. Secondary battery separator and secondary battery
[0091] The polyolefin microporous membrane of the present invention has high mechanical strength and shutdown characteristics at room temperature, and also has excellent mechanical strength at high temperature. Thus, the secondary battery separator containing the polyolefin microporous membrane of the present invention has excellent shape retention characteristics even when the secondary battery using the separator is abnormally heated, and is difficult to break even if foreign matter is mixed into the winding body or the secondary battery or mechanical deformation is applied to the secondary battery as a whole, and has high durability, so it can suppress short circuits and improve safety, and is therefore preferred.
[0092] Furthermore, a secondary battery including the secondary battery separator of the present invention is preferred because the separator is unlikely to break even when abnormal heat is generated or mechanical deformation is applied and the separator has high durability.
[0093] Example
[0094] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.
[0095] 1. Measurement and evaluation methods
[0096] The following describes the methods for measuring the various physical properties of the polyolefin microporous membranes used in the Examples. In addition, for measurements in which the number of samples to be measured is not described, only one sample was measured.
[0097] (1) Melting point of polyolefin used for polyolefin microporous membrane
[0098] The melting point of the polyolefin used in the polyolefin microporous membrane is measured by differential scanning calorimetry (DSC) based on JIS K 7121:2012. 6.0 mg of the sample was sealed in an aluminum crucible, and a differential scanning calorimeter PYRIS Diamond DSC manufactured by Parking Elmer was used. In a nitrogen atmosphere, the temperature was raised from 30°C to 230°C at 10°C / min (first heating), then maintained at 230°C for 5 minutes, cooled to 30°C at a rate of 10°C / min, and after reaching 30°C, the temperature was raised from 30°C to 230°C at a rate of 10°C / min (second heating), and each crystal melting endotherm curve was obtained. The temperature of the peak confirmed in the crystal melting endotherm curve obtained by the second heating was taken as the melting point.
[0099] (2) Enthalpy of the second DSC heating process of polyolefin microporous membranes and gel sheets
[0100] The enthalpy of the DSC second heating process of the polyolefin microporous membrane and gel-like sheet is measured by the differential scanning calorimetry (DSC) method based on JIS K7121:2012. 6.0 mg of the sample is sealed in an aluminum crucible, and the temperature is raised from 30°C to 230°C at 10°C / min (first heating) using a differential scanning calorimeter PYRIS Diamond DSC manufactured by Parking Elmer under a nitrogen atmosphere. After that, the temperature is kept at 230°C for 5 minutes, cooled to 30°C at a rate of 10°C / min, and after reaching 30°C, the temperature is raised from 30°C to 230°C at a rate of 10°C / min (second heating) to obtain each crystal melting endotherm curve. The temperature of the peak with the largest crystal melting endotherm among the peaks confirmed in the crystal melting endotherm curve obtained by the second heating is taken as the peak top temperature. In addition, a straight line baseline was set in the range of 60°C to 170°C, and the heat was calculated from the area of the portion surrounded by the straight line baseline and the crystal melting endothermic curve, and the total melting endothermic heat was calculated by converting it per unit mass of the sample. In addition, the heat was calculated from the area of the portion surrounded by the straight line baseline and the crystal melting endothermic curve before 120°C, and the heat was converted per unit mass of the sample to calculate the crystal melting endothermic heat below 120°C, and the ratio (%) to the total crystal melting endothermic heat was calculated.
[0101] (3)Film thickness
[0102] The film thickness of the polyolefin microporous membrane was measured at five locations within a range of 50 mm × 50 mm using a contact thickness meter (Light Mic VL-50, manufactured by Midoyo Co., Ltd.) (10.5 mm φ superhard spherical measuring instrument, measuring load 0.01 N). The average value was taken as the film thickness (μm) of one sample, and the average value of the measurements of three samples was taken as the film thickness (μm). (4) Mass per unit area
[0103] The mass per unit area is calculated by 2 Determination of the quality of polyolefin microporous membranes.
[0104] (5) Puncture strength calculated by mass per unit area
[0105] Regarding the puncture strength converted to unit area mass, a digital dynamometer (DS2-20N) manufactured by IMADA was used, and a needle (P-3000S-102G-10 manufactured by KATO TECH) with a diameter of 1 mm (0.5 mmR at the tip) was used to measure the maximum load value when the polyolefin microporous membrane held was punctured at a speed of 2 mm / sec in an atmosphere of 25°C, and the puncture strength converted to unit area mass was calculated by the following formula. The puncture strength converted to unit area mass is the average value of the values measured at 3 locations of the sample.
[0106] Formula: Puncture strength converted to unit area mass (gf / g / m 2 ) = maximum load (gf) / unit mass of polyolefin microporous membrane (g / m 2 )
[0107] (6) Tensile strength in the width direction (TD) at 25°C
[0108] About the tensile strength in the width direction (TD) (kgf / cm 2 ), measured under the following conditions in an atmosphere of 25°C using a tensile testing machine Instron 5543 manufactured by Instron in accordance with ASTM D882.
[0109] Sample shape: Rectangular shape: 100 mm in length and 10 mm in width
[0110] ·Measurement direction: width direction (TD)
[0111] Distance between chucks: 20mm
[0112] ·Stretching speed: 100mm / min
[0113] Grip: 2702-018 Jaw Faces for Flats (rubber coating, 50×38 mm) produced by Instron
[0114] Load sensor: 500N
[0115] Chuck pressure: 0.50MPa
[0116] Tensile strength (kgf / cm 2 ), which is obtained by dividing the strength of the sample when it breaks by the cross-sectional area of the sample before the test. For the tensile strength, the average value of the values measured at three locations on the sample is calculated.
[0117] (7) Shutdown characteristics (temperature)
[0118] The polyolefin microporous membrane was heated at a rate of 5°C / min and the air permeability was measured by an air permeometer (EGO-1T, manufactured by Asahi Seiko Co., Ltd.) to obtain an air permeability barrier of 1×10 5 sec / 100cm 3 The temperature in Air was taken as the shutdown temperature (°C) (SD temperature). The measuring unit was composed of an aluminum block with a thermocouple immediately below the polyolefin microporous membrane. A 5 cm x 5 cm square of the sample was cut and the temperature was measured while the periphery was fixed with an O-ring.
[0119] (8) Strength at 5 mm displacement in the puncture strength measurement at the closed temperature
[0120] The strength PS5 (gf / g / m 2 ), is a value obtained by measuring the maximum load value when a polyolefin microporous membrane is punctured at a speed of 2 mm / sec at the shutdown temperature calculated by the method of (6) using a compression testing machine (KES-G5) manufactured by KATO TECH with an electric hot air generator (TSK-21) and a needle with a diameter of 1 mm (the front end is 0.5 mmR). The value is obtained by the following formula.
[0121] Formula: Strength PS5 (gf / g / m 2 ) = maximum load (gf) / mass per unit area of polyolefin microporous membrane (g / m 2 )
[0122] (9) Melting point of polyolefin microporous membrane
[0123] The melting point of the polyolefin microporous membrane was measured by differential scanning calorimetry (DSC) (first heating process) based on JIS K7121:2012. 6.0 mg of the sample was sealed in an aluminum crucible, and the temperature was raised from 30°C to 230°C at 10°C / min using a differential scanning calorimeter PYRIS Diamond DSC manufactured by Parking Elmer to obtain a crystal melting endothermic curve. The temperature of the peak confirmed on the obtained crystal melting endothermic curve was taken as the melting point of the polyolefin microporous membrane.
[0124] (10) Crystal melting endothermic heat of polyolefin microporous membrane
[0125] The crystal melting endotherm of the polyolefin microporous membrane is calculated based on the results of differential scanning calorimetry (DSC) analysis according to JIS K 7121:2012. 6.0 mg of the sample was sealed in an aluminum crucible, and the temperature was raised from 30°C to 230°C at 10°C / min in a nitrogen atmosphere using a differential scanning calorimeter PYRIS Diamond DSC manufactured by Parking Elmer to obtain a crystal melting endotherm curve. For the crystal melting endotherm curve obtained during crystal melting, a straight baseline was set in the range of 60°C to 170°C, and the heat was calculated based on the area of the portion surrounded by the straight baseline and the crystal melting endotherm curve. The heat was converted to the unit mass of the sample to calculate the total crystal melting endotherm. During the heating process, the temperature at which the crystal melting endotherm reaches 10% of the total crystal melting endotherm is recorded as T. 10 , and the temperature when it reaches 50% is recorded as T 50 , calculate T 50 and T 10 The temperature difference (T 50- T10 ).
[0126] (Example 1)
[0127] The weight average molecular weight (Mw) of the polyolefin was 9.0×10 5 Ultra-high molecular weight polyethylene resin (polyethylene A, melting point 123°C, 135°C) is put into a twin-screw extruder, and liquid paraffin as a film-forming solvent is injected from the side feeder of the twin-screw extruder. The injection amount of liquid paraffin is adjusted so that the amount of polyethylene resin is 20% by weight when the total of polyethylene resin and liquid paraffin is set to 100% by weight. After injection into the twin-screw extruder, melt kneading is carried out to obtain a polyolefin resin composition mixed with polyethylene resin and liquid paraffin. The obtained polyolefin resin composition is removed from the twin-screw extruder through a filter to remove foreign matter, and then extruded from a T-die in sheet form, and cooled with a cooling roller at a temperature of 15°C to obtain a gel-like sheet. The obtained gel-like sheet is successively biaxially stretched at 115°C by a tentering method, and stretched to 6 times in both the width direction and the mechanical direction. The stretched gel-like sheet is fixed on a 30cm×30cm aluminum frame plate, immersed in a dichloromethane bath adjusted to 25°C to remove the liquid paraffin, and air-dried at room temperature. The obtained dried film was subjected to heat setting treatment at 120°C for 10 minutes.
[0128] The results are shown in Table 1. In the table, "shutdown temperature" is abbreviated as "SD temperature", "tensile strength in the width direction (TD) at 25°C" is abbreviated as "TD tensile strength", and "weight %" is abbreviated as "wt %".
[0129] (Example 2)
[0130] The weight average molecular weight (Mw) was adjusted to 9.0×10 5 60 parts by mass of ultra-high molecular weight polyethylene resin (polyethylene A, melting point 123°C, 135°C) and a weight average molecular weight (Mw) of 1.0×10 5 A gel sheet was obtained in the same manner as in Example 1 except that the mixture was melt-mixed by using a twin-screw extruder and 40 parts by weight of a high-density polyethylene resin (polyethylene F, melting point 132° C.) and 40 parts by weight of a high-density polyethylene resin (polyethylene F, melting point 132° C.) of the present invention, and the amount of liquid paraffin injected was adjusted to 27% by weight when the total of the polyethylene resin mixture and the liquid paraffin was 100% by weight. The obtained gel sheet was subjected to sequential biaxial stretching by a tentering method and stretched to 8 times in both the width direction and the machine direction. A polyolefin microporous membrane was obtained in the same manner as in Example 1 except that (in the curve of the crystal melting endotherm measured by the second temperature rise process of DSC of the gel sheet, the temperature at which the crystal melting endotherm became 10% of the total crystal melting endotherm was 107° C.).
[0131] (Example 3)
[0132] The weight average molecular weight (Mw) was adjusted to 9.0×10 5 Ultra-high molecular weight polyethylene resin (polyethylene B, melting point 108°C, 134°C) and the amount of liquid paraffin injected were adjusted to 20% by weight when the total of polyethylene resin and liquid paraffin was 100% by weight, and melt kneading was performed by a twin-screw extruder, and a gel-like sheet was obtained in the same manner as in Example 1. The obtained gel-like sheet was sequentially biaxially stretched by a tentering method and stretched to 8 times in both the width direction and the machine direction, and a polyolefin microporous membrane was obtained in the same manner as in Example 1 (in the curve of the crystal melting endotherm measured by the second temperature increase process of DSC of the gel-like sheet, the temperature at which the crystal melting endotherm became 10% of the total crystal melting endotherm was 103°C).
[0133] (Example 4)
[0134] The weight average molecular weight (Mw) was adjusted to 9.0×10 5 60 parts by mass of ultra-high molecular weight polyethylene resin (polyethylene B, melting point 108°C, 134°C) and a weight average molecular weight (Mw) of 1.0×10 5 A mixture of 40 parts by weight of a high-density polyethylene resin (polyethylene F, melting point 132° C.) and 40 parts by weight of a high-density polyethylene resin (polyethylene F, melting point 132° C.) was prepared, and the amount of liquid paraffin injected was adjusted to 27 parts by weight when the total of the polyethylene resin mixture and the liquid paraffin was 100 parts by weight. Melt kneading was performed in a biaxial extruder in the same manner as in Example 1 to obtain a gel-like sheet. The obtained gel-like sheet was sequentially biaxially stretched by a tentering method to 9 times in both the width direction and the machine direction, and the dried film after removing the liquid paraffin was heat-set at 125° C. for 3 minutes. A polyolefin microporous membrane was obtained in the same manner as in Example 1 (in the curve of the crystalline melting endotherm measured by the second temperature rise process of DSC of the gel-like sheet, the temperature at which the crystalline melting endotherm became 10% of the total crystalline melting endotherm was 106° C.).
[0135] (Comparative Example 1)
[0136] The weight average molecular weight (Mw) was adjusted to 1.5×10 6The ultra-high molecular weight polyethylene resin (polyethylene C, melting point 136°C) was added, and the amount of liquid paraffin injected was adjusted to 20% by weight when the total of the polyethylene resin mixture and the liquid paraffin was set to 100% by weight, and melt-kneading was performed by a twin-screw extruder. A gel-like sheet was obtained in the same manner as in Example 1, except that the obtained gel-like sheet was sequentially biaxially stretched by a tentering method to 7 times in both the width direction and the machine direction, and the dried film after removing the liquid paraffin was heat-set at 130°C for 10 minutes. A polyolefin microporous membrane was obtained in the same manner as in Example 1 (in the curve of the crystal melting endotherm measured by the second temperature increase process of DSC of the gel-like sheet, the temperature at which the crystal melting endotherm became 10% of the total crystal melting endotherm was 115°C).
[0137] (Comparative Example 2)
[0138] The weight average molecular weight (Mw) was adjusted to 1.5×10 6 60 parts by mass of ultra-high molecular weight polyethylene resin (polyethylene C, melting point 136°C) and a weight average molecular weight (Mw) of 1.0×10 5 A mixture of 40 parts by weight of a high-density polyethylene resin (polyethylene F, melting point 132° C.) and 40 parts by weight of a high-density polyethylene resin (polyethylene F, melting point 132° C.) was prepared, and the amount of liquid paraffin injected was adjusted to 27% by weight when the total of the polyethylene resin mixture and the liquid paraffin was set to 100% by weight, and melt-kneaded by a twin-screw extruder. A gel-like sheet was obtained in the same manner as in Example 1, except that the obtained gel-like sheet was sequentially biaxially stretched by a tentering method to 7 times in both the width direction and the machine direction. A polyolefin microporous membrane was obtained in the same manner as in Example 1 (in the curve of the crystal melting endotherm measured by the second temperature rise process of DSC of the gel-like sheet, the temperature at which the crystal melting endotherm became 10% of the total crystal melting endotherm was 113° C.).
[0139] (Comparative Example 3)
[0140] The weight average molecular weight (Mw) was adjusted to 1.5×10 6Ultra-high molecular weight polyethylene resin (polyethylene D, melting point 135°C) was added, and the amount of liquid paraffin injected was adjusted to 20% by weight when the total of polyethylene resin and liquid paraffin was set to 100% by weight, and melt-kneading was performed by a twin-screw extruder, and a gel-like sheet was obtained in the same manner as in Example 1. The obtained gel-like sheet was sequentially biaxially stretched by a tentering method, stretched to 9 times in both the width direction and the machine direction, and the dried film after removing the liquid paraffin was heat-set at 130°C for 10 minutes. A polyolefin microporous membrane was obtained in the same manner as in Example 1 (in the curve of the crystal melting endotherm measured by the second temperature increase process of DSC of the gel-like sheet, the temperature at which the crystal melting endotherm became 10% of the total crystal melting endotherm was 115°C).
[0141] (Comparative Example 4)
[0142] The weight average molecular weight (Mw) was adjusted to 1.5×10 6 60 parts by mass of ultra-high molecular weight polyethylene resin (polyethylene D, melting point 135°C) and a weight average molecular weight (Mw) of 1.0×10 5 A mixture of 40 parts by weight of a high-density polyethylene resin (polyethylene F, melting point 132°C) and 40 parts by weight of liquid paraffin, and the amount of liquid paraffin injected was adjusted to 27 parts by weight when the total of the polyethylene resin mixture and the liquid paraffin was set to 100 parts by weight, and melt-kneading was carried out by a twin-screw extruder. Otherwise, a polyolefin microporous membrane was obtained in the same manner as in Example 1 (in the curve of the crystalline melting endotherm measured by the second heating process of DSC of the gel-like sheet, the temperature at which the crystalline melting endotherm became 10% of the total crystalline melting endotherm was 113°C).
[0143] (Comparative Example 5)
[0144] The weight average molecular weight (Mw) was adjusted to 1.5×10 6 70 parts by mass of ultra-high molecular weight polyethylene resin (polyethylene C, melting point 136°C) and a weight average molecular weight (Mw) of 1.0×10 5A gel sheet was obtained in the same manner as in Example 1 except that the mixture was melt-kneaded by a twin-screw extruder and 30 parts by weight of a high-density polyethylene resin (polyethylene F, melting point 132° C.) and the amount of liquid paraffin injected was adjusted to 20% by weight when the total of the polyethylene resin mixture and the liquid paraffin was 100% by weight. The obtained gel sheet was simultaneously biaxially stretched by a tentering method to 8 times in both the width direction and the machine direction, and the dried film after removing the liquid paraffin was heat-set at 130° C. for 10 minutes. A polyolefin microporous membrane was obtained in the same manner as in Example 1 except that (in the curve of the crystal melting endotherm measured by the second temperature rise process of DSC of the gel sheet, the temperature at which the crystal melting endotherm becomes 10% of the total crystal melting endotherm is 115° C.).
[0145] (Comparative Example 6)
[0146] The weight average molecular weight (Mw) was adjusted to 1.5×10 6 70 parts by mass of ultra-high molecular weight polyethylene resin (polyethylene C, melting point 136°C) and a weight average molecular weight (Mw) of 7.0×10 5 A mixture of 30 parts by weight of a high-density polyethylene resin (polyethylene E, melting point 126° C.) and 30 parts by weight of a high-density polyethylene resin (polyethylene E, melting point 126° C.) was prepared, and the amount of liquid paraffin injected was adjusted to 20% by weight when the total of the polyethylene resin mixture and the liquid paraffin was set to 100% by weight, and melt-kneading was performed by a twin-screw extruder. A gel-like sheet was obtained in the same manner as in Example 1, except that the obtained gel-like sheet was simultaneously biaxially stretched by a tentering method to 8 times in both the width direction and the machine direction, and the dried film after removing the movable paraffin was heat-set at 130° C. for 10 minutes. A polyolefin microporous membrane was obtained in the same manner as in Example 1 (in the curve of the crystalline melting endotherm measured by the second temperature increase process of DSC of the gel-like sheet, the temperature at which the crystalline melting endotherm becomes 10% of the total crystalline melting endotherm is 115° C.).
[0147] [Table 1]
[0148]
Table 1
[0149]
[0150] [Table 2]
[0151]
[0152] (evaluate)
[0153] In the puncture strength measurement at the shutdown temperature of the polyolefin microporous membranes of Examples 1 to 4, the strength at a displacement of 5 mm was recorded as PS5, and it was confirmed that PS5 was 7.0 gf / g / m 2 The polyolefin microporous membranes of Comparative Examples 1 to 6 all had a PS5 of 7.0 gf / g / m 2 The following indicates that the mechanical strength at high temperature is insufficient.
[0154] Industrial Availability
[0155] The polyolefin microporous membrane of the present invention has excellent mechanical strength at high temperatures, and therefore, when used as a battery separator, it can maintain high safety even when the battery temperature rises. Therefore, it can be preferably used as a secondary battery separator that requires high capacity.
Claims
1. A polyolefin microporous membrane, wherein the temperature at which the crystal melting endotherm measured in the first heating process by differential scanning calorimetry becomes 50% of the total melting endotherm is recorded as T 50 The temperature at which 10% of the total melting heat is absorbed is recorded as T 10 When the polyolefin microporous membrane satisfies T 50 -T 10 ≥15℃, when the strength at the time of displacement of 5mm in the puncture strength measurement conducted at the closed temperature is recorded as PS5, PS5 is 7.0gf / g / m 2 above.
2. The polyolefin microporous membrane according to claim 1, wherein the puncture strength calculated as the mass per unit area measured at 25°C is 55 gf / g / m 2 above. 3 . The polyolefin microporous membrane according to claim 1 , wherein the melting point measured in the first heating process by differential scanning calorimetry is 130° C. or higher and 140° C. or lower.
4. The polyolefin microporous membrane according to claim 1 or 2, wherein the tensile strength in the width direction TD measured at 25°C is 2100 kgf / cm 2 above. The polyolefin microporous membrane according to claim 1 or 2, which has a shutdown temperature of less than 133°C. The polyolefin microporous membrane according to claim 1 or 2, which has a membrane thickness of 10 μm or less. 7 . The polyolefin microporous membrane according to claim 1 , wherein the polyolefin constituting the polyolefin microporous membrane contains polyethylene as a main component. 8 . A secondary battery separator comprising the polyolefin microporous membrane according to claim 1 . 9 . A secondary battery comprising the secondary battery separator according to claim 8 .
Citation Information
Patent Citations
Method for producing thermoplastic resin microporous membrane
JP2002256099A
Microporous polyethylene film
JP2006321841A
Microporous polyolefin membrane, separator for secondary batteries, and secondary battery
WO2020195380A1
Polyolefin micro porous film, laminate, and battery
WO2021033733A1